(3QSGdI aj GdejQGKs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg (B... (3bGd YdeGDfG QMege Gddg QMege Gddg jJYdb HJQcI GdejJ Mbhb CQHYI eQJHI ChdG ojHJOC HJcajfg hJLgjRg ef ZjQ JHPjQ hdG JbJjQ Ke JbVj Ojhfg ef LejY eG Hbj ef eGdg Ke JfaP hUGjGg (B...s
(3BNQgG (B:s
... (3hCeG YUhHJg SbhW SOS , hLOg eG Ef JQc HfJG WjHG hHfJ GHf hRhL Ch RhLG SbhW fUa SOS Yf QHY (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis